The Relationship Between Illness Perception and Religiosity on Medication Adherence Among Type 2 Diabetes Mellitus Patients at Puskesmas Lampihong - Helenisa, Helenisa; Manto, Onieqie Ayu Dhea; Cynthia Eka F. T, Cynthia Eka F. T; Tasalim, Rian (INDOGENIUS, 2025)
Background & Objective: Adherence to medication is a key factor in controlling Diabetes Mellitus; however, challenges in patient compliance are still frequently encountered. Illness perception and religiosity have been shown to have a significant impact on adherence levels. Preliminary data from Lampihong Health Center indicate an increase in DM cases, yet medication adherence remains low, highlighting the need for an in-depth study of the influencing factors. This study aims to analyze the relationship between illness perception and religiosity and their impact on medication adherence among patients with type 2 diabetes mellitus receiving treatment at the Lampihong Health Center. Methods: This study employs a cross-sectional design with a descriptive correlational approach. A total of 30 type 2 DM patients were selected using an accidental sampling technique. Data were collected using the Illness Perception Questionnaire, Religious Involvement Questionnaire, and the Morisky Medication Adherence Scale. Pearson correlation tests were used for data analysis. Results: A significant relationship was found between illness perception and religiosity with medication adherence (p < 0.05). Patients with positive illness perceptions and higher religiosity levels tend to have better medication adherence. Conclusion: A positive illness perception and high religiosity can enhance medication adherence in type 2 DM patients. These findings provide a basis for developing interventions that consider psychosocial and spiritual aspects in the management of DM at the local level.